Spatial Planning Of Peripheral Rural Regions In Serbia - Marija Maksin; Sasa Milijic; Nikola Krunic (European Regional Science Association (ERSA), 2012)
After the establishment of the new legislative framework on planning and construction, territorial organization of the Republic of Serbia and regional development, as well as adoption of the Spatial Plan of the Republic of Serbia 2010-2020 (SPRS), the strategic spatial plans at regional level have been elaborated. Over the last few years, the total of 10 regional spatial plans (RSP) have been either adopted or in final stage of elaboration, five of them for peripheral rural regions of Serbia. The paper analyzes concepts and models used in planning the sustainable territorial development of peripheral, rural and mountain regions in Serbia. It refers to several key questions of sustainable territorial development of peripheral regions: accessibility, urban-rural development, rural settlement network and depopulation of peripheral mountain areas, tourism development, sustainable natural resources utilization and potentials for trans-border cooperation. One of the models discussed is for rural settlement network. Aging of rural population and depopulation of peripheral mountain regions hinders the preservation of micro rural centers, in particular the provision of public and commercial services. Emerging model is of mobile services, now developed dominantly for social and medical services, which can be expanded to almost all services, or combined with the revitalization of micro rural centers, namely those within urban centers' gravity zone, main transport corridors or tourism destinations. Potentially most attractive tourism assets are located at peripheral regions of Serbia. Spatial pattern of assets allows for dispersed development of tourist nodes, gateways and paths. The question is how much of dispersion or concentration in the spatial pattern of tourism infrastructure and supply is acceptable and sustainable. The benefits and constraints for implementing some of proposed models are discussed. Short critical overview on constrains of regional development and implementation of regional spatial plans related to undeveloped regional level of governance, as well as to weak vertical and horizontal coordination of other levels of governance has been indicated. The purpose of this paper is to discuss the challenges and possibilities of regional spatial planning to contribute sustainable regional territorial development of peripheral and rural regions.
Keywords: 330